The relationship between entrepreneurial orientation and employees performance at Malpro Industri Sdn Bhd in Selangor / Nor Fazillah Jefri Sukumar - mohd Jefri Sukumar, Nor Fazillah (2018)
Entrepreneurial orientation (EO) is a dimension of strategy-making process that related to employees performance in organization based on (Wiklund & Shepherd, 2005). Entrepreneurial orientation such as innovativeness, proactiveness, competitive aggressiveness, risk-taking and autonomy had a positive relationship on employee’s performance in the organization. Entrepreneurial orientation has a significant impact on employees performance as they can sustain their interest in helping and develop the organization based on their entrepreneurship to achieve the organizational goals. The main objective of this research is to identify the relationship between entrepreneurial orientation and employees performance at Malpro Industri Sdn. Bhd. in Selangor. From the finding, all the independent variables which is innovativeness, proactiveness, competitive aggressiveness, risk-taking and autonomy were found to have a positive and strong significant correlation with employees performance The second objective is to identify the dimension of entrepreneurial orientation that is most practiced by employees of Malpro Industri Sdn. Bhd. in Selangor. Based on the result of the descriptive statistics, researcher can concluded that risk-taking is the most entrepreneurial orientation dimension that practiced in Malpro Industri Sdn. Bhd. that affect employees performance with highest mean value which compared than competitive aggressiveness dimension that has a lowest mean value practiced in Malpro Industri Sdn. Bhd. This research was conducted by distributing questionnaire among Malpro Industri Sdn. Bhd. employees. There was 108 employess selected randomly to participate in this research. This study is significant to Malpro Industri Sdn. Bhd. in helping them to knowing the relationship between entrepreneurial orientation and employees performance at the organization.